CdS quantum dots confined in mesoporous TiO2 with exceptional photocatalytic performance for degradation of organic polutants. (July 2017) - Zhou, Panpan; Xie, Yu; Fang, Jing; Ling, Yun; Yu, Changling; Liu, Xiaoming; Dai, Yuhua; Qin, Yuancheng; Zhou, Dan
Abstract: In this paper, the mesoporous TiO2 with different concentration of CdS quantum dots (i.e., x% CdS/TiO2 ) was successfully fabricated by the sol-gel method. The composition, structure and morphology of the nanocomposites were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), UV–vis diffuse reflectance spectroscopy (UV–Vis/DRS) and nitrogen physical adsorption test and so on. The proportion of CdS and TiO2 is very important for the photocatalytic performance. As a result, the photocatalytic degradation performance from the most to the least is in the order of 2% CdS/TiO2, 4% CdS/TiO2, 8% CdS/TiO2, pure TiO2 and 1% CdS/TiO2 . The photocatalytic (PC) activity of the 2% CdSTiO2 is characterized by photocatalytic degradation of methyl orange, which can be completely degraded within 45 min better than 60 min TiO2 takes. It is also much better than CdS. Moreover, other four organic pollutants, such as methylthionine chloride, bisphenol A, rhodamine B, malachite green can also be degraded quickly on the condition of 2% CdS/TiO2 . What's more, the chemical stability and cycling capability of 2% CdS/TiO2 are reflected by five cyclic degradation of methyl orange. Highlights: CdS/TiO2 with different concentration of CdS quantum dots are prepared. The size of the CdS is about 10 nm demonstrating the existence of CdS QDs. CdS/TiO2 is characterized by photocatalytic degradation of five organic pollutants. 2% CdS/TiO2 shows the best photocatalytic performance. The chemical stability and cycling capability of 2% CdS/TiO2 are tested.